2015
DOI: 10.1016/j.celrep.2015.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DISC1 Disruption in hiPSCs Alters Wnt Signaling and Neural Cell Fate

Abstract: Summary Genetic and clinical association studies have identified disrupted-in-schizophrenia 1 (DISC1) as a candidate risk gene for major mental illness. DISC1 is interrupted by a balanced chr(1;11) translocation in a Scottish family, in which the translocation predisposes to psychiatric disorders. We investigate the consequences of DISC1 interruption in human neural cells using TALENs or CRISPR-Cas9 to target the DISC1 locus. We show that disruption of DISC1 near the site of the translocation results in decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 68 publications
(82 reference statements)
10
115
0
Order By: Relevance
“…596 genes were differentially expressed in neurons derived from schizophrenic patients versus controls, reflecting the phenotypic differences between the differentiated neuronal populations (Brennand et al, 2011). Previous work has shown that schizophrenia hiPSC-derived NPCs have aberrant migration (Brennand et al, 2014b) and cellular polarity (Yoon et al, 2014), perturbed WNT signaling (Srikanth et al, 2015; Topol et al, 2015b), increased oxidative stress (Brennand et al, 2014b; Paulsen et al, 2011; Robicsek et al, 2013) and altered responses to environmental stressors (Hashimoto-Torii et al, 2014); while schizophrenia hiPSC-derived neurons exhibit decreased neurite number (Brennand et al, 2011), reduced synaptic maturation (Brennand et al, 2011; Robicsek et al, 2013; Wen et al, 2014; Yu et al, 2014) and synaptic activity (Wen et al, 2014; Yu et al, 2014), and blunted activity-dependent response (Roussos et al, 2016). Extensive immunocytochemical validation of the NPC lines used in the present study showed they are positive for diverse NPC markers including nestin, Sox2, vimentin, Pax6 and TBR2(Brennand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…596 genes were differentially expressed in neurons derived from schizophrenic patients versus controls, reflecting the phenotypic differences between the differentiated neuronal populations (Brennand et al, 2011). Previous work has shown that schizophrenia hiPSC-derived NPCs have aberrant migration (Brennand et al, 2014b) and cellular polarity (Yoon et al, 2014), perturbed WNT signaling (Srikanth et al, 2015; Topol et al, 2015b), increased oxidative stress (Brennand et al, 2014b; Paulsen et al, 2011; Robicsek et al, 2013) and altered responses to environmental stressors (Hashimoto-Torii et al, 2014); while schizophrenia hiPSC-derived neurons exhibit decreased neurite number (Brennand et al, 2011), reduced synaptic maturation (Brennand et al, 2011; Robicsek et al, 2013; Wen et al, 2014; Yu et al, 2014) and synaptic activity (Wen et al, 2014; Yu et al, 2014), and blunted activity-dependent response (Roussos et al, 2016). Extensive immunocytochemical validation of the NPC lines used in the present study showed they are positive for diverse NPC markers including nestin, Sox2, vimentin, Pax6 and TBR2(Brennand et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Subject selection criteria vary in these studies, spanning from specific genetic abnormalities like CNVs such as 22q11.2 deletion [3840], 15q11.2 deletion [41] or CNTNAP2 deletion [42] and mutations such as DISC1 mutation [43,44] to SCZ patients with no identified genetic risk factor drawn from clinical populations [4548]. Childhood onset SCZ (COS) [49], has also been studied since COS exhibits more severe psychopathology as compared to adult onset SCZ and thus would likely have a more robust cellular phenotype.…”
Section: Recent Ipsc-based Cellular Models Of Sczmentioning
confidence: 99%
“…In these studies, the neural populations generated, range from neural progenitor cells (NPC) [4143,45,46,48,49,52] to mixed neural populations [3840,47,53] and to more specific neural subtypes such as highly enriched glutamatergic neurons [44]. These iPSC-derived neural populations recapitulate the normal developmental time frame and more closely resemble fetal neural progenitors and neuronal populations, suitable for analysis of developmental abnormalities.…”
Section: Recent Ipsc-based Cellular Models Of Sczmentioning
confidence: 99%
“…Heterozygous STXBP1 mutations decreased spontaneous and evoked neurotransmitter release, again supporting the role of synaptic development deficits in SZ pathology. Using TALENs and CRISPR/Cas9, Young-Pearse and colleagues disrupted DISC1 near the site of the chromosome translocation found in the Scottish pedigree and found increased WNT signaling in iPSC-derived NPCs [35]. Notably, while these studies provide important insight into loss-of-function phenotypes and basic biology of these risk genes in human NPCs and neurons, patient-specific mutations may have a different net effect on gene expression, as in the case of the 4bp deletion in DISC1 that was shown to be a gain-of-function mutation [36].…”
Section: Selection Of Patient Cohorts For Disease Modelingmentioning
confidence: 99%